Ex vivo evaluation of anterior lens capsule staining in horses with three concentrations of gentian violet for surgical training - Bettio, Marcelle; Seibel, Maiara Poersch; Franceschini, Maria Eduarda Mattos; Rocha, Rafaella Silva; Baptista, Renata Lima; Pigatto, Anita Marchionatti [UNESP]; Pigatto, Joao Antonio Tadeu (Univ Federal Goias, 2023)
The aim of this study was to evaluate and compare the effectiveness of three concentrations of gentian violet (0.5%, 0.1% and 0.05%) for staining the anterior capsule of the lens in horses. Thirty-six post-mortem equine eyes were collected. The eyes were subdivided into three groups composed of 12 eyes each, according to the concentration of gentian violet used. The effectiveness of staining the anterior capsule of the lens with different concentrations of gentian violet was assessed using an empirical system of evaluation on adequate or inadequate staining of capsular flaps. Based on the evaluation of the examiner, the 0.1% and 0.05% concentrations of gentian violet allowed adequate visualisation of the anterior capsule for continuous curvilinear capsulotomy training, whereas the 0.5% concentration produced strong and inadequate capsular staining. The model developed using gentian violet at concentrations of 0.1% and 0.05% allowed a clear visualisation of the capsular flap, which makes it viable as a model for training the continuous curvilinear capsulotomy step in cataract surgery in horses.
Keywords: anterior capsulotomy; vital dyes; equine; wet lab; surgical training